Perceived Audit Quality, Earnings Management and Cost of Debt Capital: Evidence from the Energy Listed Firms on Vietnam's Stock Market - Thu, Phung Anh; Khanh, Thai Hong Thuy; Ha, Nguyen Tran Thai; Khuong, Nguyen Vinh (International Journal of Energy Economics and Policy, 2018)
This study examines the impact of perceived audit quality and accrual-based earnings management on cost of debt capital of the energy listed firms on Vietnam's stock market. Our data set includes 29 energy companies on Vietnam stock markets (HNX and HOSE) in the period from 2010 to 2016. We used FEM and REM estimator to test our hypotheses. The results confirm that there is no significant statistical association between accrual-based earnings management and cost of debt. There is a negative association between audit quality, firm size, return on assets and cost of debt while firm leverage and the tangible asset has a positive association. Moreover, global financial crisis has no statistically significant influence on the cost of debt capital. The research results have implications for regulators and investors about the stability of the economy in emerging markets. Keywords: cost of debt, earnings management, audit quality, energy enterprises, Vietnam. JEL Classifications: M42; G32 DOI: https://doi.org/10.32479/ijeep.6992